2015
DOI: 10.17221/51/2015-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping for adult-plant leaf rust resistance genes in Chinese wheat cultivar Weimai 8

Abstract: Wang J., Li Z., Shi L., Zhu L., Ren Z., Li X., Liu D., Shah S.J.A. (2015): QTL mapping for adult-plant leaf rust resistance genes in Chinese wheat cultivar Weimai 8. Czech J. Genet. Plant Breed., 51: 79-85.The wheat cultivar Weimai 8 is a good source of adult-plant resistance to leaf rust in China. In order to understand the genetic background of the resistance genes, 179 F 2:3 families derived from the cross Weimai 8 and Zhengzhou 5389 (susceptible to leaf rust) were used to construct a linkage map. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
1
5
1
Order By: Relevance
“…The present study was aimed to repeat the analysis with greater precision and focusing on stripe rust rather than leaf rust. For instance, [45] reported a single major QTL, QLr.hbau-2AS, derived from Weimai 8 flanked by Xcfd36 and Xbarc1138 markers with an interval length of 2.58 cM. However, the present study identified four QTLs derived from Weimai 8 APR to stripe rust.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…The present study was aimed to repeat the analysis with greater precision and focusing on stripe rust rather than leaf rust. For instance, [45] reported a single major QTL, QLr.hbau-2AS, derived from Weimai 8 flanked by Xcfd36 and Xbarc1138 markers with an interval length of 2.58 cM. However, the present study identified four QTLs derived from Weimai 8 APR to stripe rust.…”
Section: Discussioncontrasting
confidence: 62%
“…The work described herein is the continuation of [45], that performed a study of F 2:3 population from a similar cross population using SSR markers. The present study was aimed to repeat the analysis with greater precision and focusing on stripe rust rather than leaf rust.…”
Section: Discussionmentioning
confidence: 99%
“…The search for additional sources of resistance to rust diseases can be conducted using extensive germplasm collections representing different genetic backgrounds and origins ( Kokhmetova et al, 2011 ; Badoni et al, 2017 ; Kumar et al, 2019 ). Linkage mapping has been commonly used to identify QTLs associated with resistance to SR ( Wang et al, 2015 ; Chen et al, 2018 ), LR ( Xue et al, 2018 ; Kthiri et al, 2018 ), and YR ( Zeng et al, 2019 ). This method was also successfully applied in QTL mapping for LR and SR resistance in Kazakhstan ( Genievskaya et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pinto da Silva et al (2018) summarized leaf rust resistant QTL from a large number of published papers. On chromosome 2AS, QTL for adult plant resistance were found in wheat cultivars from Europe (Kumar et al, 2013), Canada (Singh et al, 2013), and China (Wang et al, 2015). On chromosome 4BS, QTL for adult plant resistance were found in cultivars from Europe (Azzimonti et al, 2014;Messmer et al, 2000;Schnurbusch et al, 2004), CIMMYT (Chhuneja et al, 2006;Rosewarne et al, 2015), Australia (Ponce-Molina et al, 2018), Canada (Singh et al, 2013), Brazil (Kolmer et al, 2018), and China (Han et al, 2016).…”
Section: Discussionmentioning
confidence: 99%